2019
DOI: 10.1101/795294
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Geometric Sharpness on Translucent Material Perception

Abstract: When judging optical properties of a translucent object, humans often look at sharp geometric features such as edges 4 and thin parts. Analysis of the physics of light transport shows that these sharp geometries are necessary for scientific 5 imaging systems to be able to accurately measure the underlying material optical properties. In this paper, we examine 6 whether human perception of translucency is likewise affected by the presence of sharp geometry, by confounding our 7 perceptual inferences about an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 53 publications
2
8
0
Order By: Relevance
“…One possibility is that the diagnostic features for translucent perception lie in the edge/corner of a translucent object and our rugged objects included much information to judge translucency. More recently, Xiao et al (2020) investigated the effect of geometry on translucency perception. In their experiments, they changed the smoothness of the object edges.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that the diagnostic features for translucent perception lie in the edge/corner of a translucent object and our rugged objects included much information to judge translucency. More recently, Xiao et al (2020) investigated the effect of geometry on translucency perception. In their experiments, they changed the smoothness of the object edges.…”
Section: Discussionmentioning
confidence: 99%
“…First, the physical process of translucency is complex, involving surface reflection and subsurface scattering (see Gkioulekas, Xiao, Zhao, Adelson, Zickler, & Bala, 2013 ; Xiao, Walter, Gkioulekas, Zickler, Adelson, & Bala, 2014 for detailed description of physical model of subsurface scattering and translucency perception). Previous work shows that physical material properties, lighting, shape, and context all affect the appearance of translucent objects ( Chowdhury, Marlow, & Kim, 2017 ; Fleming & Bülthoff, 2005 ; Gigilashvili, Shi, Wang, Pedersen, Hardeberg, & Rushmeier, 2021 ; Gigilashvili, Thomas, Hardeberg, & Pedersen, 2021 ; Marlow & Anderson, 2021 ; Marlow, Kim, & Anderson, 2017 ; Motoyoshi, 2010 ; Nagai, Ono, Tani, Koida, Kitazaki, & Nakauchi, 2013 ; Sawayama, Dobashi, Okabe, Hosokawa, Koumura, Saarela, et al, 2019 ; Tamura, Higashi, & Nakauchi, 2018 ; Xiao et al, 2014 ; Xiao, Zhao, Gkioulekas, Bi, & Bala, 2020 ), and it still remains unknown how humans extract intrinsic translucent material properties from images. Second, there are many different kinds of translucent materials in real life.…”
Section: Introductionmentioning
confidence: 99%
“…Using rendered images, most previous works have measured translucent appearance using a single task (e.g. asking observers to rate the apparent translucency, asking observers to judge which of the two images seems to be more translucent, or matching the images based on the perceived translucency by using a slider to adjust one particular physical parameter) ( Motoyoshi, 2010 ; Nagai et al, 2013 ; Xiao et al, 2020 ). Such measurements may not fully reflect how humans perceive and recognize translucent materials in the real world.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it has been demonstrated that changing the direction of lighting was associated with a significant impact on the translucency consistency of the human teeth as in some cases, failure was noticed. 18,19 A previous investigation compared the parallel and perpendicular directions of the transmitted light intensities concerning the proximal surface of the tooth to investigate the light fluxes-related directional dependence. 20 The authors have estimated mean values of 2.88, and 0.86 for the parallel and perpendicular transmitted intensities of light for dentin and enamel, respectively.…”
Section: Discussionmentioning
confidence: 99%